x*ln(x*x)+ln(2)=0

Simple and best practice solution for x*ln(x*x)+ln(2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x*ln(x*x)+ln(2)=0 equation:


Simplifying
x * ln(x * x) + ln(2) = 0

Multiply x * x
x * ln(x2) + ln(2) = 0

Multiply x * ln
lnx * x2 + ln(2) = 0

Multiply lnx * x2
lnx3 + ln(2) = 0

Reorder the terms for easier multiplication:
lnx3 + 2ln = 0

Reorder the terms:
2ln + lnx3 = 0

Solving
2ln + lnx3 = 0

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(2 + x3) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(2 + x3)' equal to zero and attempt to solve: Simplifying 2 + x3 = 0 Solving 2 + x3 = 0 Move all terms containing l to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x3 = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x3 = 0 + -2 x3 = 0 + -2 Combine like terms: 0 + -2 = -2 x3 = -2 Add '-1x3' to each side of the equation. x3 + -1x3 = -2 + -1x3 Combine like terms: x3 + -1x3 = 0 0 = -2 + -1x3 Simplifying 0 = -2 + -1x3 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -2x=2x+8 | | 11/2x-3/4=1/6 | | N=G-18 | | 2x-1+x+4+36=2x+46 | | 3x+y=45 | | 8(2t-9)=-88 | | 2(f-10)=-34 | | -10(s+2)=-95 | | F(-4)=2x^/x-1 | | -2=-3(2x+4) | | 3(4x-1)=8 | | 3(4s+6)=174 | | ab+c=5solvec | | x^2+22x+115=0 | | 2n+4sobren+1n=2 | | 6(x+7)=-2(5-x) | | -2x=-2x+8 | | 4=4(5x-6) | | 4(2x+7)=9 | | =(2x-5)(3x+8)+7 | | 2n+4sobren+1=2 | | an=n/(n-1),n≥2 | | 14x+2=-2x | | 6/7=42 | | 5a^2+26a-63=0 | | 9x+16=4c | | 88/21=x | | 2200/525=x | | 2200/525 | | (3z/8)-7=-6 | | 11.6=1.5(x+0.15-3.5) | | 2+3yi=(x-1)+3i |

Equations solver categories